PROPHETIC LEADERSHIP STRATEGIES OF SCHOOL PRINCIPALS IN IMPROVING GRADUATE QUALITY AT SDIT AL-ITTIHAD SUKABUMI AND SD AISYIYAH ISLAMIC CENTER CIANJUR - Ulfah Nurfadilah; Akhmad Fauzi Hamzah (Academic Bright Collaboration, 2026)
This study examines prophetic leadership strategies of school principals in improving graduate quality in Islamic elementary schools, addressing the limited empirical studies that explain how prophetic values are operationalized within school leadership practices and their contribution to educational outcomes. The study aims to develop a conceptual understanding of the relationship between prophetic leadership and graduate quality improvement. A qualitative approach with a multi-case study design was employed in SDIT Al-Ittihad Sukabumi and SD Aisyiyah Islamic Center Cianjur. Data were collected through participatory observation, in-depth interviews, and documentation involving principals, teachers, education staff, foundation administrators, school committees, and parents. Data analysis followed data condensation, data display, conclusion drawing, and cross-case analysis, with validity ensured through source and method triangulation. The findings indicate that both principals integrate the prophetic values of Siddiq, Amanah, Tabligh, and Fathanah into school management, although through different approaches. SDIT Al-Ittihad Sukabumi emphasizes participatory leadership, exemplary conduct, and religious culture, while SD Aisyiyah Islamic Center Cianjur adopts data-driven governance, structured communication, and instructional innovation. In both schools, prophetic values strengthen organizational culture, teacher professionalism, stakeholder collaboration, and learning quality, contributing to graduates with academic competence, Islamic character, and 21st-century skills. The study offers a practical framework for translating prophetic values into leadership practices, governance systems, and teacher development programs. The model may support principal development and quality assurance processes in Islamic schools. As the study is limited to two schools, the findings should be interpreted within their specific contexts. This study proposes a conceptual model of prophetic leadership strategy that links prophetic values, leadership practices, organizational culture, and graduate quality, contributing to the development of Islamic educational leadership theory and offering practical insights for school leadership improvement.